Citizenship education and common European values in the digital age - Tomé, V. (Presidential Conference "Contribution of education to the promotion of common European values and democratic citizenship" (04/10/2023), 2023)
2025 will be the European Year of Digital Citizenship Education (DCEY2025), which aims to promote digital citizenship and digital literacy, including AI literacy, in educational institutions. It will address the challenges and opportunities presented by the digital age and it is an excellent opportunity to empower citizens on European common values (human dignity, freedom, democracy, equality, rule of law, human rights) to foster an inclusive, tolerant, fair, supportive and non-discriminatory society. The Council of Europe, which proposed the DCEY2025, will work in close cooperation with the European Commission, UNESCO, OECD and other organisations, contributing to the SDG4. DCEY2025 provides a platform to set common goals, share practices and measure impacts. Every country can promote the initiative, coordinate activities, involve other institutions and organisations, contributing to Europe-wide activities and cooperate with other countries.